The Effectiveness And Impact Of Allied Health Professionals In Patient Care: A Systematic Review Of The Roles Of Surgeons, Nurses, Operating Room Technicians, Dentists, And Laboratory Personnel (The Review of Diabetic Studies, 2025)
Background: Allied health professionals form the cornerstone of multidisciplinary healthcare systems, contributing to diagnosis, treatment, rehabilitation, and the overall continuum of patient care. The collaboration among surgeons, nurses, operating room (OR) technicians, dentists, and laboratory personnel ensures efficient service delivery, enhances patient safety, and optimizes health outcomes. However, the effectiveness and impact of these diverse roles in improving clinical efficiency, patient satisfaction, and healthcare quality remain under continuous evaluation. Objective: This systematic review aimed to evaluate the effectiveness and impact of allied health professionals—specifically surgeons, nurses, OR technicians, dentists, and laboratory personnel—on patient care outcomes across various healthcare settings. Methods: A systematic literature search was conducted using PubMed, Scopus, Web of Science, and CINAHL databases from 2010 to 2025. Keywords included “allied health professionals,” “interdisciplinary care,” “patient outcomes,” “surgeons,” “nurses,” “operating room technicians,” “dentists,” and “laboratory personnel.” Studies were included if they quantitatively or qualitatively evaluated the contributions of these professionals to patient outcomes, care quality, and interprofessional collaboration. Data extraction focused on performance indicators such as mortality reduction, procedural safety, diagnostic accuracy, and patient satisfaction. Results: A total of 78 studies met inclusion criteria. Evidence demonstrated that collaborative care involving surgeons and nurses significantly reduced postoperative complications and hospital readmissions. Operating room technicians were found to enhance surgical efficiency and reduce intraoperative errors through technical expertise and equipment management. Dentists played a crucial role in early detection of systemic diseases, contributing to preventive care and improved quality of life. Laboratory personnel were pivotal in accurate diagnosis and monitoring of disease progression, directly influencing clinical decision-making and treatment efficacy. Across all groups, interprofessional communication and continuous training emerged as critical determinants of patient safety and care quality. Conclusion: Allied health professionals collectively enhance the efficiency, safety, and quality of patient care through specialized expertise and teamwork. Strengthening interprofessional collaboration, implementing evidence-based training programs, and promoting shared decision-making are key to maximizing their impact. Future research should explore standardized performance metrics and the integration of advanced technologies to further optimize the roles of these professionals in patient-centered care.